The correlation of Alkaline Phosphatase, lactate dehydrogenase, C-Reactive protein, erythrocyte sedimentation rate, and apparent diffusion coefficient values with Enneking staging and osteosarcoma subtypes - Febrian, Firas; Mahyudin, Ferdiansyah; Setiawati, Rosy; Edward, Mouli; Mustokoweni, Sjahjenny; Utomo, Budi (Edelweiss Applied Science and Technology, 2024)
Apparent diffusion coefficient (ADC) values obtained from Magnetic Resonance Imaging (MRI) have shown potential as predictors of osteosarcoma staging and subtype, along with laboratory results for alkaline phosphatase (ALP), lactate dehydrogenase (LDH), c-reactive protein (CRP), and erythrocyte sedimentation rate (ESR). However, studies investigating this correlation are still relatively limited. These tests may be an alternative for osteosarcoma staging and subtyping, especially in low-resource settings. This study aims to investigate the correlation between the ADC value and laboratory findings with the staging and subtype of osteosarcoma. This retrospective study analyzed data from osteosarcoma patients from August 2021 to August 2023, including serum levels of ALP, LDH, CRP, ESR, and ADC values from MRI. A study of 39 osteosarcoma patients found that most were male (61.5%), with an average age of 19. The distal femur was the most common tumor location (33.3%), and osteosarcoma chondroblast type was the predominant subtype (30.8%). Enneking stage IIB was the most prevalent (79.5%). ALP, LDH, CRP, and ESR biomarkers significantly correlated with Enneking staging (p<0.05). However, no correlations were found between these biomarkers and osteosarcoma subtype (p>0.1). Additionally, no significant correlations were observed between the mean ADC and Enneking staging (p=0.061) or osteosarcoma subtype (p=0.084). ALP, LDH, CRP, and ESR levels have a strong and significant correlation to the staging of Enneking osteosarcoma. However, the mean ADC values on MRI do not have a significant correlation to the osteosarcoma subtype based on histopathology.